OPTIMALISASI PERKEMBANGAN REMAJA MELALUI PEMBENTUKAN KEMBALI PUSAT INFORMASI KONSELING REMAJA (PIK-R) DI SMAS LANCANG KUNING KELURAHAN BUMI AYU - Fadhila Rahman; Dwi Yulia Pratiwi; Aura Anisa Simarmata; Fittri Handayani; Aulia Rahma Dhani; Enjelika Aristi; Helma Yani; Vanessa Putri Irawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Adolescent development tasks include various aspects such as the formation of self-identity, development of social skills, and emotional adjustment which often face various challenges. In this case, the Youth Counseling Information Center (PIK-R) plays an important role in providing the necessary support so that teenagers can overcome these problems effectively at the Lancang Kuning Dumai Private High School ( SMAS). This research aims to empower students to develop various social and learning skills by preparing and implementing the PIK-R program which includes socialization, training and peer counseling practices. Data collection was carried out through participatory observation of village officials, school principals and students involved. The results show that this program is running well with full support from the school and has succeeded in increasing students' knowledge and skills in peer counseling and adolescent health. This program is also expected to improve and optimize Youth Counseling Services at SMAS Lancang Kuning Dumai.